The Cardio Respiratory Endurance Level of the Penjaskesrek Gymnastics Instructors in the Education and Teacher Training Faculty of Universitas Syiah Kuala - Jafar, Muhammad (The Journal of Educational Development, 2018)
This research is entitled "The Cardio respiratory Endurance Level of the Physical Education, Health, and Recreation (henceforth: Penjaskesrek) Gymnastics Instructors in the Education and Teacher Training Faculty (FKIP) of Universitas Syiah Kuala". Endurance is one of the major factors of physical fitness. Endurance is closely related to activities or daily work of human beings in doing jobs or moving. High endurance can maintain physical abilities in a relatively long period of time continuously. This study aimed to describe the level of cardio respiratory endurance of the Gymnastics Instructors in FKIP of Syiah Kuala University. The research question is how are the endurance level of the cardio respiratory endurance of the Gymnastics Instructors in FKIP of Syiah Kuala University. The population in this research was all of the 16 Penjaskesrek Gymnastics Instructors in the Faculty of Education and Teacher Training of Syiah Kuala University, while the samples were drawn by means of purposive sampling technique. The data used in this study were drawn using cardiac respiratory endurance test. The obtained data were analyzed in terms of their averages and percentages. The results show that the obtained values are as follows. (1) The average level of the cardio respiratory endurance obtained from the test is 15.07 and is in the "Medium âcategory; (2) in general, the average level of the cardio respiratory endurance of the Gymnastics Instructors are just 0 person or 0% in the "trained" category,  2 persons or 12.5% in the "very good" category, 4 persons or 25% in the "good" category,  7 persons or 43.75% in the "medium" category, and 3 persons or 18.75% in the "poor" category. Based on the results of this research, it is suggested that all Gymnastics instructors in the University have good cardio respiratory as well as other physical endurance, and are capable of well performing their duties as gymnastics instructors and improving their exercise and ability so that they perform their duties better.